Contrasting cryptofaunal responses to seabird nutrient inputs illuminate coral reef productivity pathways - Laura‐Li Jeannot; Ruth E. Dunn; M. Joyce P. Velos; Gareth J. Williams; Cassandra E. Benkwitt; Nicholas A. J. Graham; Simon J. Brandl (Ecology, 2026)
Nutrients moving across ecosystems can propagate through food webs via distinct trophic pathways. Their integration into food webs is often mediated by small, abundant taxa that channel subsidies from primary producers to higher trophic levels. On coral reefs, cryptobenthic fishes and invertebrates can fill these roles, yet their responses to allochthonous nutrients are poorly understood. We compared cryptofaunal communities and associated trophic dynamics across nutrient‐rich islands with intact seabird populations and nutrient‐poor rat‐infested islands in the Chagos Archipelago, Indian Ocean. Specifically, we evaluated how the presence of seabird colonies influenced cryptofaunal nutrient assimilation, biomass, structure, and isotopic niche dynamics, and how these shifts propagated to mesopredators and higher order piscivorous and invertivorous fishes. Most cryptobenthic fishes and some invertebrates showed nutrient enrichment near seabird colonies. Although the isotopic niches of cryptobenthic fishes and invertebrates overlapped, niche widths diverged in nutrient‐rich environments, with invertebrates exhibiting broader niches and cryptobenthic fishes remaining comparatively constrained, reflecting differential access to shared resources. Mixing models also reflected a shift toward cryptobenthic fishes in the diet of a mixed carnivore near seabird colonies. Community patterns revealed strong asymmetries: Nutrient‐rich reefs supported twice the amount of cryptobenthic fish biomass and a 10‐fold increase in larger piscivorous fish productivity, while reefs near rat‐infested islands were characterized by relatively greater cryptic invertebrate biomass and higher invertivore productivity. Taken together, these results suggest that cryptobenthic fishes' capacity to capitalize on seabird nutrients may allow them to exert competitive dominance and top‐down control over invertebrates in nutrient‐rich environments, thereby amplifying piscivorous pathways, while nutrient‐poor environments appear to favor invertebrates and their consumers. Rather than reflecting uniform biomass loss under rat invasion, these patterns indicate a shift in trophic routing from fish‐mediated to invertebrate‐mediated energy channels. Our findings demonstrate that cross‐ecosystem nutrient vectors do not simply enhance reef productivity but reorganize trophic structure. Therefore, invasive species that sever these linkages can drive the emergence of alternative food‐web configurations with distinct energetic pathways.